The relationship of inclusion, control, and affection to marital intactness or separation and gender - Kallookaran, Thomas Cherian (Animo Repository, 1996)
This study determines the relationship of Inclusion, Control and Affection to marital intactness or separation, and to finds out whether there is a significant interaction effect of marital status and gender on expressed and wanted inclusion, control, and affection. It also aims to find out the differences between separated males and males in intact marriages, separated females and females in intact marriages, males and females in intact marriages, and separated females and males. A descriptive research design was used, employing the survey method through the use of questionnaire as a tool for gathering data. The subjects of the study were 15 separated males, 15 males from intact marriages, 15 separated females, and 15 females from intact marriages from Metro Manila. Pearson r and a two-way analysis of variance were employed to find out the relationship and differences, respectively. Hypotheses were tested at .05 level of significance. The findings of the study showed no significant relationship between marital status and wanted and expressed inclusion, control, and affection. However, a significant interaction effect for wanted control and wanted affection was found. Besides, a significant difference was found between separated males and males in intact marriages in the areas of expressed and wanted control, and wanted affection between males and females in intact marriages in the areas of expressed and wanted control and between separated males and females in the area of wanted affection. No significant difference was shown between separated females and females in intact marriages in any of the areas. Based on the findings it was concluded that interpersonal dimensions of inclusion, control, and affection do not have a significant relationship with marital intactness or separation of married couples. Responsibility of the males and their expressions of affection and intimacy are important factors of marital satisfaction, while irresponsibility of the males and their lack of affection and intimacy contribute to marital conflicts and eventual separation. Besides, the male dominance in marital relationships gives the greatest probability to be intact. Further study has been suggested on a bigger sample to confirm the findings of the study.